Aberrant right subclavian artery causing megaoesophagus in three cats. (7th May 2018) - Cinti, F.; Della Santa, D.; Borgonovo, S.; Bussadori, R.; Troiano, D.; Pisani, G.
Abstract : Three entire, domestic, shorthair male cats (age range: 3 months to 5 years) were referred because of regurgitation. Megaoesophagus attributable to aberrant right subclavian artery, originating from the aorta at the level of the fourth intercostal space, was diagnosed in all cats using thoracic radiography and CT angiography. One cat had concurrent patent ductus arteriosus with a normal aortic arch. Three‐dimensional volume‐rendered CT images were used to assess the malformations and to plan surgery for the treatment of the vascular anomalies. Different surgical approaches were used in the two kittens. The third cat was not operated. CT angiography is well suited for preoperative planning in cats with aberrant right subclavian artery alone or in combination with other vascular anomalies.